2007
DOI: 10.1682/jrrd.2006.10.0131
|View full text |Cite
|
Sign up to set email alerts
|

Stroke caregiver information needs: Comparison of Mainland and Puerto Rican caregivers

Abstract: Abstract-Research indicates that informal caregivers of stroke survivors often do not have the information necessary to adequately manage the recovery process at home. This article presents findings on the information sources and needs of stroke caregivers both in Puerto Rico and the Mainland United States. Data were collected from 120 caregivers (42 Puerto Rican, 78 Mainland) of veterans who had experienced a stroke. Of all caregivers, 22% to 50% reported the need for information related to stroke recovery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Seven studies achieved a response rate above 60%, 72, 7476, 78, 79, 81 six utilized reliable and valid measurements, 74, 7781 and seven assessed statistical significance. 72, 74, 7680 All mixed-methods studies appraised using MMAT used the methodology appropriately, used relevant sources to collect the qualitative and quantitative data, and had sample representing the population. Although the integration of qualitative and quantitative approaches was relevant for three studies, 82, 83, 85 none of the studies discussed the limitations of integrating qualitative and quantitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies achieved a response rate above 60%, 72, 7476, 78, 79, 81 six utilized reliable and valid measurements, 74, 7781 and seven assessed statistical significance. 72, 74, 7680 All mixed-methods studies appraised using MMAT used the methodology appropriately, used relevant sources to collect the qualitative and quantitative data, and had sample representing the population. Although the integration of qualitative and quantitative approaches was relevant for three studies, 82, 83, 85 none of the studies discussed the limitations of integrating qualitative and quantitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…The caregivers identify the information and training skills required to implement physical care as the most important of pre-discharge needs 14 . Care giving is a very important task that post-stroke disabled patients understand very little and the informal caregivers make an important contribution to supply disabled stroke survivors at home 15,16 . Previous researches demonstrate that stroke survivors and their caregivers often lack the information necessary to help manage the recovery process at home 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Those with training tend to have less anxiety and stress and this help elders to engage in social relationships, to be optimistic about their future, to cope successfully with stressful situations and to feel in control of their lives. Also caregiving make people confident about their own abilities and a higher proportion of disabled stroke survivors achieved independence at an earlier stage 15,20 . Furthermore, the needs of patients and their caregivers require ongoing nursing assessment and adaptation of interventions in response to changing needs to optimize quality of life for both the patient and family caregiver 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Hinojosa and Rittman (2007) surveyed caregivers of stroke veterans (N = 120), and found the top needs for information to be about stroke and its implications and managing the care recipient's behaviors/emotions, recovery process, and safety at home. Likewise, King and Semik (2006) surveyed caregivers of stroke survivors (N = 93) and concluded that caregivers have three general categories of unmet needs: a) preparing for caregiving (e.g., contact with peers, learning care and skills), b) enhancing stroke survivor function (e.g., equipment, therapy, social-recreational), and c) sustaining the self and family (e.g., respite care, peer sharing, and legal/financial advice).…”
Section: Introductionmentioning
confidence: 99%